PENGARUH PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA FLIPBOOK TERHADAP HASIL BELAJAR SISWA PADA MATERI IPAS DI KELAS III SDN 4 TOMILITO - Djafar, Dita Pratiwi D.; Panai, Abdul Haris; Kudus, Kudus; Nurfadliah, Nurfadliah; Arif, Rifda Mardian (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This study aims to describe the influence of the Problem Based Learning (PBL) Model Assisted by Flipbook Media on Student Learning Outcomes in Science Material in Class III SDN 4 Tomilito. The research method used is the pre-experimental design of One Group Pretest-Postest. This study uses data collection techniques through observation, testing, and documentation. The sample in this study was 20 students of class III SDN 4 Tomilito. The difference in learning outcomes can be seen in the average pre-test and post-test scores Based on the pretest score results of 60.2, the posttest score results were 82.2. Indicating that the use of the Problem Based Learning model assisted by Flipbook media on student learning outcomes in science material is very influential. The average N-Gain data or the difference between the pretest and posttest results of student learning outcomes in science material in class III SDN 4 Tomilito is included in the medium criteria, namely 0.54, the N-Gain function to measure the effectiveness of learning. From the data above, it can be concluded that there is an influence of the use of the Problem Based Learning model assisted by Flipbook media on student learning outcomes in the science material in class III of SDN 4 Tomilito. ABSTRAKPenelitian ini bertujuan mendeskripsikan terdapat Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Flipbook Terhadap Hasil Belajar Siswa Pada Materi IPAS Di Kelas III SDN 4 Tomilito. Metode penelitian yang digunakan yaitu pre-eksperimental desain One Grup Pretest-Postest. Penelitian ini menggunakan teknik pengumpulan data melalui observasi, tes, dan dokumentasi. Sampel dalam penelitian ini adalah siswa kelas III SDN 4 Tomilito sebanyak 20 siswa. Perbedaan hasil belajar terlihat pada nilai rata-rata skor pre-test dan post-test Berdasarkan hasil skor pretest 60,2 hasil skor postes 82,2. Menandakan penggunaan model Problem Based Learning berbantuan media Flipbook terhadapa hasil belajar siswa pada materi IPAS begitu berpengaruh. Data hasil rata- rata N-Gain atau selisih hasil pretes dan postes hasil belajar siswa pada materi IPAS di kelas III SDN 4 Tomilito termasuk kriteria sedang yaitu 0,54, fungsi N-Gain untuk mengukur efektivitas suatu pembelajaran. Dari data diatas maka dapat disimpulkan bahwa terdapat pengaruh penggunaan model Problem Based Learning berbantuan media Flipbook terhadap hasil belajar siswa  pada materi IPAS di kelas III SDN 4 Tomilito.